The midnight man eaudiobook - Mitchell, Caroline (Slayton Thriller., 2021)
Audie Awards 2022 Finalist in the Mystery category A THRILLING NEW SERIES FROM THE NUMBER ONE BESTSELLER CAROLINE MITCHELL 'Twisty, tense and creepy as hell... I loved it!' - K.L. SLATER ' Will keep you on the edge of your seat' - ALICE HUNTER _______ 'I remember the day I died quite clearly.' Blackhall Manor has witnessed many dark crimes, long before five teenage girls break in to play the Midnight Game. It was supposed to be a game, but only four girls come home. Detective Sarah Noble has just returned to the force, and no one knows more about Blackhall Manor than her. Except perhaps Elliott Carter, who is only seven but has seen things in his dreams most adults could never imagine. It's a case that will bring them together and shake Sarah to her core. Will she be ready to meet the Midnight Man? A gripping and twisty thriller, perfect for fans of C. J. Tudor, Cara Hunter and Alex North. _______ PRAISE FOR THE MIDNIGHT MAN 'Caroline Mitchell at her dark and twisty best' - Teresa Driscoll, bestselling author of I Am Watching You 'Creepy, captivating and clever' - Helen Fields , bestselling author of Perfect Remains ' A spine tingling, creepy book that you'll struggle to put down' - John Marrs , bestselling author of The One 'Creepy and intense' - Mel Sherratt , bestselling author of Ten Days 'Terrifying, mysterious and suspenseful' - Patricia Gibney, author of The Missing Ones 'A tense and deliciously creepy read' - D.S. Butler , author of On Cold Ground 'If you like early Stephen King you'll love THE MIDNIGHT MAN' - Robert Dugoni , New York Times bestseller 'A spooky, twisty mystery with a spine-chillingly creepy ending' - Susi Holliday, author of The Last Resort